La Bob Jones University : hier et aujourd’hui - Mokhtar Ben Barka (Revue LISA)
This article examines the separatist beliefs and practices at Bob Jones University. Firstly, it shows that despite the recent changes, this institution still represents the old face of fundamentalist higher education. Secondly, this essay focuses on the controversy around Republican candidate George W. Bush’s appearance at Bob Jones University.